Resource Split Full Duplex to Mitigate Inter-Cell Interference in Ultra-Dense Small Cell Networks - Haesoon Lee; Yosub Park; Daesik Hong (IEEE Access, 2018)
When a full duplex (FD) system is used in a multi-cell environment, the simultaneous transmission and reception cause an increase in inter-cell interference compared with half duplex (HD) systems. This problem is more severe in ultra-dense small cell network (UDN) environments where small cells are extremely dense. Therefore, the performance gain of FD transmission over traditional HD transmission is significantly degraded by this increase in inter-cell interference. To overcome the performance loss, we consider a new FD operation that can avoid the increased inter-cell interference caused by FD use. The basic idea involves separating the small cell base stations into two groups and using half of the communication resources in a manner similar to HD systems. We compare the performance of conventional HD and FD with the proposed scheme in terms of network throughput. Network throughput physically refers to the total throughput per unit area of the network. The simulation results consider indoor and outdoor scenarios and show that our proposed scheme outperforms conventional FD and conventional HD.